Kedudukan Kepala Otorita Ibu Kota Nusantara Sebagai Pengelola Keuangan Negara Berdasarkan Kekuasaan Presiden Menurut Konsepsi Keuangan Negara - Rusmana, Rizki Tri; Ardilafiza; Illahi, Beni Kurnia (Jurnal Ilmiah Kutei, 2023)
The head of the Nusantara's authority has been granted the power to manage the finances of the Nusantara's Capital by the President, even though it is not explicitly stated in the State Finances Act. This has led to confusion about the nature of the financial management authority referenced in the Nusantara's Capital Law. This study aims to examine the institutional characteristics of the Nusantara's Capital Authority and the position of its Head as a manager of state finances, based on the President's power according to the concept of state finance. Using a normative law approach with a statute and conceptual approach, the research found that the Nusantara's Capital Authority has been established based on national law, with its headquarters in the national capital and directly responsible to the President, without a Regional House of Representatives and not led by a governor. Given these characteristics, it is more appropriate to categorize the Nusantara's Capital Authority as a Central Government. In terms of managing state finances in the Nusantara's Capital, the Head of the Authority is in the position of a minister/head of an institution as referred to in paragraph (2) letter b, serving as the Budget User/Goods User for Nusantara's Capital.